2012
DOI: 10.11120/beej.2012.19000006
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Skills in Undergraduate Students. A Ten-year Survey of a Plant Physiology Course

Abstract: In the health and life sciences, as well as in other scientific disciplines, problem solving depends on mathematical skills. However, significant deficiencies are commonly found in this regard in undergraduate students. In an attempt to understand the underlying causes and to improve students' performance, this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…It has been suggested that an increase in the percentage of mathematical questions left unanswered in examinations may be due to low self-efficacy of the students [7]. The results obtained for the online tests in the present work confirm this suggestion.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…It has been suggested that an increase in the percentage of mathematical questions left unanswered in examinations may be due to low self-efficacy of the students [7]. The results obtained for the online tests in the present work confirm this suggestion.…”
Section: Discussionsupporting
confidence: 85%
“…LeBard et al [6] indicated that students experience difficulties in transforming their mathematical training into a form that allows them to use it effectively. Low scores for questions that require the application of mathematical skills in undergraduate students of Plant Physiology have also been reported [7] and, additionally despite the number of mathematical questions in the examinations being low, the students' performance in such questions was a good predictor of the final grade, as also shown by Mulhern et al [8] for Psychology undergraduates.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations